IMPLEMENTASI PELAPORAN KEUANGAN DESA TERHADAP TERCAPAINYA PROGRAM KERJA DESA KAWAK TAHUN 2024 - Priyanto, Agus; Budi Santoso, Nugroho (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Financial reporting is an essential obligation for any party utilizing a budget, whether in government or the private sector. Through financial reports, one can evaluate the achievement of work programs. If the programs are successfully implemented, this will be reflected in the completed financial statements.This study employs a qualitative method with a descriptive approach, aimed at examining how financial reporting is implemented in relation to the achievement of work programs in Kawak Village in 2024.Financial reporting is one of the indicators of a village’s progress and serves as a benchmark to assess whether a program is running effectively. Data collection in this research was conducted through interviews, observation, and documentation to obtain both primary and secondary sources.The findings show that the implementation and administration of financial management in Kawak Village, Pakisaji Sub-district, Jepara Regency, has been effective and aligned with the applicable regulations, specifically Minister of Home Affairs Regulation Number 77 of 2020. This regulation emphasizes key financial management principles, including transparency, accountability, efficiency, and compliance.This is evidenced by the budget accountability reports prepared by the village treasurer, as well as regular administrative and functional responsibilities carried out as required. As a result, the work programs in the village have been successfully achieved.